Legal Certainty of Land Sale with Buyback Right as an Alternative Financing Option for Real Estate Companies in Legal Reform Efforts - Bahori Ahoen (Pusat Publikasi Nusantara, 2025)
The buy-sell transaction with the right of repurchase is a practice commonly found in society. However, from a legal perspective, there is much debate surrounding the validity of this type of transaction. Therefore, in this dissertation, the author raises several issues: How is the legal certainty of buy-sell transactions with the right of repurchase as an alternative financing method? How is the legal protection for the parties involved in such agreements? And what is the future legal reform perspective regarding buy-sell transactions with the right of repurchase? The research method used in this study is normative-empirical juridical, supported by interviews. The data sources are obtained from literature-based research documents. The results of the study show that legal certainty regarding buy-sell transactions with the right of repurchase in Indonesian law has not yet been well established. This is because the provisions previously regulated under Articles 1519 and 1532 of the Indonesian Civil Code are no longer applicable following the enactment of Law No. 5 of 1960. In addition, inconsistent rulings by the Supreme Court have further contributed to legal uncertainty in this matter. As for legal protection, there is no specific regulation that protects the parties involved in buy-sell transactions with the right of repurchase. Consequently, many issues related to the rights and obligations of the parties are brought to court. It is crucial for the parties to fully understand their respective rights and obligations, create clear and detailed agreements, and consider all legal and financial aspects before entering into such transactions. Legal reform regarding buy-sell transactions with the right of repurchase is an urgent necessity to ensure that this scheme can function optimally as a legal, safe, and efficient alternative financing method. Regulatory frameworks governing buy-sell transactions with the right of repurchase are needed, as well as the establishment of dispute resolution institutions specifically for financing schemes based on such transactions.